Multifunctional applications and research advances of low-molecular-weight heparin - Zhang, Yanru; Guo, Shuixian; Xu, Jingchao (Frontiers in Pharmacology, 2025)
Low-molecular-weight heparin (LMWH) is a class of anticoagulant drugs derived from the controlled depolymerization of heparin. LMWH possesses a lower molecular weight and a shorter glycan chain length than unfractionated heparin (UFH), resulting in higher bioavailability, a more predictable pharmacokinetic profile, and consequently, a more convenient administration route. These characteristics make LMWH a primary choice for thromboprophylaxis of deep vein thrombosis. LMWH is clinically indicated for the prevention and treatment of venous thromboembolic diseases. Its role in obstetric complications, inflammation modulation, and antitumor therapy is also increasingly being recognized. The objective of this review was to systematically summarize the progress of LMWH research and to thoroughly explore its mechanisms of action and clinical indications. By analyzing the advantages and disadvantages of LMWH, evaluating its safety and adverse reactions, discussing the challenges in its clinical application, and proposing future research directions, in this review, we aim to promote the application and development of LMWH in a broader range of fields.